1988
DOI: 10.1083/jcb.107.4.1589
|View full text |Cite
|
Sign up to set email alerts
|

Role of laminin and basement membrane in the morphological differentiation of human endothelial cells into capillary-like structures.

Abstract: Abstract. We have defined a signal responsible for the morphological differentiation of human umbilical vein and human dermal microvascular endothelial cells in vitro. We find that human umbilical vein endothelial cells deprived of growth factors undergo morphological differentiation with tube formation after 6-12 wk, and that human dermal microvascular endothelial cells differentiate after 1 wk of growth factor deprivation. Here, we report that morphological differentiation of both types of endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
670
3
3

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,120 publications
(703 citation statements)
references
References 18 publications
27
670
3
3
Order By: Relevance
“…These functions are essential steps for neovessel sprouting (Kubota et al, 1988;Connolly et al, 1989) and angiogenesis, which is an important biological process involved in metastasis formation (Liotta et al, 1991;Weidner et al, 1991). Importantly, throughout the experiment with the CAM model, this study showed NAMI-A to prevent in vivo angiogenesis at doses known to have anti-metastasis activity.…”
Section: Discussionmentioning
confidence: 62%
“…These functions are essential steps for neovessel sprouting (Kubota et al, 1988;Connolly et al, 1989) and angiogenesis, which is an important biological process involved in metastasis formation (Liotta et al, 1991;Weidner et al, 1991). Importantly, throughout the experiment with the CAM model, this study showed NAMI-A to prevent in vivo angiogenesis at doses known to have anti-metastasis activity.…”
Section: Discussionmentioning
confidence: 62%
“…Matrigel (0.5 ml at a concentration of 10-12 mg/ml) was pipetted into 13-mm-diameter tissue culture wells and polymerized at 37°C for 30 minutes to 1 hour (15,16). MSCs and EL-MSCs from SSc patients and controls were plated (6 ϫ 10 4 cells/ml) in IMDM with 1% FBS.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, high titers of AECA in patients with SLE are associated with an active lesion of the kidney and vasculitis, and it has therefore been suggested that the AECA titer could be used as a measure of renal involvement (16). Microvascular endothelial cells carry a specific antigen profile that is quite different from the profiles of the large vessels (17,18). In BD, vasculitis mainly involves capillaries and small vessels (2,3).…”
Section: Aeca Against ␣-Enolase In Behç Et's Disease 2031mentioning
confidence: 99%